Exploring tropical fisheries through fishers' perceptions: Fishing down the food web in the Tonlé Sap, Cambodia. (16th November 2017) - KC, K. B.; Bond, N.; Fraser, E. D. G.; Elliott, V.; Farrell, T.; McCann, K.; Rooney, N.; Bieg, C.
Abstract: Tropical fisheries are among the most productive fisheries in the world, often providing the primary source of protein for the local population. Despite their importance, data on these systems are relatively limited, thus hampering management and policy development. Here, the implications of increasing fishing pressure are explored by critically evaluating the perceptions of the fishers who rely on these ecosystems to survive. A total of 169 fishers in 26 different fish‐dependent communities in the Tonlé Sap Lake, Cambodia, were surveyed to understand their perceptions of the impact that fishing has had on the ecosystem. The Tonlé Sap is one of the largest, yet poorest studied, freshwater fisheries in the world. Consistent with "fishing down the food web" theory of fisheries, survey data revealed that although fishers observed the total size of fish catch remaining consistent over recent years there has been a drastic decline in the size of individual fish, as well as a reduction in the diversity of species caught. These perceptions are examined with reference to food web theories that explore how fishing pressure leads to ecosystem change, including the more recent "indiscriminate fisheries" theory.